2021
DOI: 10.1016/s0140-6736(21)00132-x
|View full text |Cite
|
Sign up to set email alerts
|

Delivering health interventions to women, children, and adolescents in conflict settings: what have we learned from ten country case studies?

Abstract: Armed conflict disproportionately affects women, newborns, children, and adolescents. Our study presents insights from a collection of ten country case studies aiming to assess the provision of sexual, reproductive, maternal, newborn, child and adolescent health and nutrition (abbreviated to women's and childern's health, i.e WCH in this paper) interventions in conflict-affected settings in Afghanistan,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 21 publications
(23 reference statements)
1
74
0
Order By: Relevance
“…For example, a case study from Afghanistan noted that comprehensive emergency obstetric and newborn care is inaccessible in most provinces. 67 A common thread in this review was the need to strengthen the support systems for midwives to enable them to provide quality services. Additionally, evidence suggests that lifesaving reproductive, maternal, newborn, child and adolescent health services frequently become disrupted in HFS.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a case study from Afghanistan noted that comprehensive emergency obstetric and newborn care is inaccessible in most provinces. 67 A common thread in this review was the need to strengthen the support systems for midwives to enable them to provide quality services. Additionally, evidence suggests that lifesaving reproductive, maternal, newborn, child and adolescent health services frequently become disrupted in HFS.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Additionally, evidence suggests that lifesaving reproductive, maternal, newborn, child and adolescent health services frequently become disrupted in HFS. 67 A paper synthesising findings from 10 case studies from conflict settings found that essential maternal and newborn health interventions were not clearly prioritised. Also, predefined packages of priority services were commonly not agreed on or implemented.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…The above issue of insecurity and its implications on women or even health workers was described and discussed in a recent article on delivering health interventions for women in conflict settings. Syria was one of 10 case studies that were described in that article ( 21 ).…”
Section: Discussionmentioning
confidence: 99%